An adaptive content based H.264/AVC rate control in low bit rate video - Chen, Fu-Chuang; Hsu, Yi-Pin (International journal of electronics and communications, 2011)
In this paper, we analyze a rate control formula, which is Laplacian based model, then propose a content based equation for an enhanced JVT-G012 algorithm. Based on the simple and fast characteristics of the JVT-G012 algorithm, which is very suitable for real time embedded systems, we integrate the equation into the JVT-G012 algorithm to create an efficient quantizer. However, active local motion will produce error distortion and influence the determination of the quantization parameter. To solve this problem, a modified histogram based detector is proposed. Combining this detector with the equation refines the predicted quantization parameter more precisely. It is shown both theoretically and experimentally that a well-designed quantizer not only improves video quality, but also maintains the designed bit rate budget. In addition, our algorithm can achieve superior results to existing algorithms-up to 0.72dB without large computation loading.